A Comparison of Perioperative Management of Anomalous Aortic Origin of a Coronary Artery Between an Adult and Pediatric Cardiac Center. (November 2016) - Herrmann, Jeremy L.; Goldberg, Leah A.; Khan, Abigail M.; Partington, Sara L.; Brothers, Julie A.; Mascio, Christopher E.; Spray, Thomas L.; Kim, Yuli Y.; Fuller, Stephanie
Background: Anomalous aortic origin of a coronary artery (AAOCA) presents in varying age-groups. Assuming management algorithms differ between pediatric and adult institutions, we compared the perioperative management of patients with AAOCA at two such centers. Methods: A retrospective review was conducted at a pediatric and an adult institution of patients 14 years or older who underwent surgical repair of AAOCA between January 2000 and May 2014. Results: Twenty patients from the pediatric center (median age: 16.5 years, range: 14-18 years) and nine patients from the adult center (median age: 40 years, range: 37-52 years) were included. An anomalous aortic origin of a right coronary artery was the most frequent pathology at each institution. Chest pain was the most common presenting symptom at both institutions. Preoperative echocardiography was performed in 95% patients at the pediatric center and in 100% of patients at the adult center. Cardiac catheterization was utilized more frequently at the adult center, and cardiac magnetic resonance imaging more commonly employed at the pediatric center. Isolated coronary unroofing was performed in 19 of 20 cases at the pediatric center and in only 2 (22%) cases at the adult institution, both by congenitally trained cardiac surgeons. More concomitant cardiac procedures were performed at the adult center with associated longer operative times and hospital stays. Conclusion: Management strategies for AAOCA vary depending on both patient-specific factors and expertise of the managing team. Further studies are needed to optimally standardize diagnostic and treatment pathways regardless of location venue.